2004
DOI: 10.1111/j.1751-1097.2004.tb00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Larval and Adult Emission Spectra of Bioluminescence in Three European Firefly Species

Abstract: We studied the spectral characteristics of the larvae of three sympatric Belgian species of fireflies, Lampyris noctiluca, Phosphuenus hemipterus and Lamprohiza splendidula. An in vivo spectral study was performed to compare bioluminescence spectra. The emission spectrum of a laboratory reared female L. noctiluca was recorded by a different, more exact method. The mean peak wavelength (kmm = 546 nm) and shapes of the unimodal emission spectra are visually similar for the larvae of all three species. The emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…). Similar to our findings, the larvae of three species of European fireflies show little light color variation and produce green light, with peak wavelengths of 546 nm (from the ventral surface: De Cock ), and Brazilian Cratomorphus larvae emit at 550 nm (Viviani et al. ).…”
Section: Discussionsupporting
confidence: 89%
“…). Similar to our findings, the larvae of three species of European fireflies show little light color variation and produce green light, with peak wavelengths of 546 nm (from the ventral surface: De Cock ), and Brazilian Cratomorphus larvae emit at 550 nm (Viviani et al. ).…”
Section: Discussionsupporting
confidence: 89%
“…Briefly, each dummy female consisted of a plastic funnel trap (volume: ~1 litre) that had a green 5 mm light emitting diode (LED) mounted on the top and in the centre of the funnel's mouth (Figure 1a). The peak emission wavelength of the LED was ~560 nm, mimicking the glow of a live female common glow-worm (Tyler 2002;De Cock 2004), and it was powered by two standard AA dry batteries (Figure 1a). We constructed dummy females of two brightness and hence expected attractiveness (Hopkins et al 2015) levels.…”
Section: Methodsmentioning
confidence: 99%
“…The European glowworm Lampyris noctiluca female emits green BL that peaks near 555 nm (DeCock, 2004) to which the species' nonbioluminescent flying males are phototactically attracted (Dreisig, 1971). Booth et al (2004) investigated whether phototaxis in the glowworm involves interactions between two spectral classes of photoreceptors, blue and green, and found that it was so.…”
Section: Is There Color Vision In Fireflies?mentioning
confidence: 99%